A economia solidária e o projeto de outra mundialização - Luiz Inácio Gaiger (Universidade do Estado do Rio de Janeiro, 2004)
The striking events of the World Social Forums, succeeded by the entry of new actors into the Brazilian political scenario launched in 2003, involved a set of both promising and unknown new possibilities for the solidarity economy. The understanding of such moments, signaling both future advances and questions, requires examining recent steps in order to unveil the meaning of the new pathways and the demands they raise, given the new choices that need to be made. This article discusses the formulations of militant praxis in the solidarity economy and analyzes some of the problems permeating its history in recent years, based primarily on empirical studies on its evolution in the State of Rio Grande do Sul in relation to actual experiences and mediating organizations. The paper identifies some of the necessary changes and innovations in the conceptualization and implementation of the solidarity economy, in the sense of expanding its frontiers and legitimizing and agglutinating its various watersheds and expressions in order to establish it as an effective pillar for an alternative development and globalization process.